Peran konselor dalam mewujudkan sekolah aman dan damai bagi siswa - Fajar Bilqis; Teten Karina; Imas Cucu Latipah (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2019)
The study was motivated by the issue that schools do not yet have an adequate environment for children's development, as evidenced by the rampant cases of violence, conflict & excessive conformity between students. The focus of the discussion was to describe the role of the counselor in creating a safe and peaceful school for students. The results of the discussion showed that the role of counselors in creating safe and peaceful schools can be both preventive and curative. Safe and peaceful schools are the basis for building healthy personalities for students